“Jan de Dood en sy bende”: Vergestaltings van die dood in die romans van Lettie Viljoen/Ingrid Winterbach - Human, Thys (Tydskrif vir letterkunde, 2018)
References to death and mortality play an (increasingly) important role in the works of Lettie Viljoen/Ingrid Winterbach. In this article the central role of personifications of death in her novels is investigated. There are mainly two important ways in which death is embodied in her novels since 1993, i.e. as an ubiquitous, but simultaneously absent male figure, such as Jama in Karolina Ferreira (translated as The Elusive Moth, 1993, 2005), Jan de Dood in Buller se plan (Buller’s plan, 1999) and Theo Verwey in Die boek van toeval en toeverlaat (The book of coincidence and refuge, 2006) and the femme fatale and angel of death, respectively represented by a seductive woman with red hair and pale skin and either an emaciated woman in black, or a black woman as in Landskap met vroue en slang (Landscape with women and snake, 1996) Buller se plan and Niggie (translated as To Hell with Cronjé, 2002, 2007). These personifications function as so-called memento mori – iconographic reminders of mortality. Although death obtains a specific personal appearance through personification, it does not become more knowable or representable in the works of Viljoen/Winterbach, however. In fact, these embodiments repeatedly rather underline the ungraspable nature and unknowableness of death. In the novels since Karolina Ferreira there is, eventually, a sustained tension between the attempts to make death more knowable and representable on the one hand and, on the other, the understanding or concession that all these attempts are, ultimately, insufficient and limited.